IMPROVING THE STUDENTS’ READING FLUENCY OF RECOUNT TEXT THROUGH MULTIMEDIA RUNNING TEXT AT THE TENTH GRADE OF SMA NEGERI 1 GUNUNGSITOLI IN 2022/2023 - Hulu, Agusman; Laoli, Adieli; Harefa, Afore Tahir; Zebua, Elwin Piarawan (Academy of Education Journal, 2023)
The method used in the research was one qualitative research is classroom action research. The purpose of this research is to improve the students reading fluency of recount text through multimedia running text at the tenth grade of SMA Negeri 1 Gunungsitoli in 2022/2023. Based on the result of the data in cycle I showed that there are 17 students in fair level (47%), there are 12 students in fairly good level (33%), there are 2 students in good level (5,60%), and there are 5 students in very good level (14,00%) and the average of students’ value is 62,6. Cycle II, there are 19 students in very good level (53%), there are 17 students in excellent level (47%) and get the average of students value is 87,36. It means that the students’ ability in reading fluency of recount text through multimedia running text in cycle II is success. Based on the result of the study, it can be concluded the multimedia running text improves the students’ reading fluency of the tenth grade of SMA Negeri 1 Gunungsitoli.